Alluvial aquifer characterisation and resource assessment of the Molototsi sand river, Limpopo, South Africa - David Walker; Nebo Jovanovic; Richard Bugan; Tamiru Abiye; Daniell du Preez; Geoff Parkin; John Gowing (Journal of Hydrology: Regional Studies, 2018)
Study region: Molototsi sand river, Limpopo, South Africa. Study focus: Ephemeral sand rivers are common throughout the world’s dryland regions, often providing a water source where more conventional sources are unavailable. However, these alluvial aquifers are poorly represented in the literature. Extensive field investigations allowed estimation of stored water volume and characterisation of an alluvial aquifer. New hydrological insights for the region: Computed alluvial aquifer properties included hydraulic conductivity of 20–300 m/d, porosity of 38–40%, and aquifer thickness of 0–6 m. Dykes and other subcrops commonly compartmentalise the aquifer though do not form barriers to flow. A hydraulic disconnect between deep groundwater (occurring in fractured metamorphic rocks) and the alluvial aquifer was revealed by groundwater levels and contrasting hydrochemistry and stable isotope signatures. The dominant recharge process of the alluvial aquifer is surface runoff occurring from torrential tributaries in the catchment’s upper reaches. A fraction of available storage is currently abstracted and there exists potential for greater exploitation for smallholder irrigation and other uses. Keywords: Aquifer properties, Conceptual model, Resource assessment, Sand river, South Africa